Formulation development of Domperidone buccal bioadhesive hydrophilic matrix tablets - Madgulkar, Ashwini R; Bhalekar, Mangesh R; Ner, Amruta S; Wable, Nitin D (Asian Journal of Pharmaceutics (AJP), 2014)
Buccoadhesives have long been employed to improve the bioavailability of drugs undergoing significant hepatic first pass metabolism. Domperidone is also reported to have low oral bioavailability due to an extensive hepatic first-pass effect. Buccoadhesive hydrophilic matrices containing Domperidone were prepared using a 32 factorial design.The amounts of Carbopol 934P (CP) and Methocel K100LV (HPMC) were taken as the formulation variables (factors) for optimizing bioadhesion and kinetics of dissolution. A mathematical model was generated for each response parameter. Bioadhesive strength tended to vary quite linearly in an increasing order with an increasing amount of each polymer. The drug release pattern for all the formulation combinations was found to be non Fickian, approaching zero-order kinetics. A suitable combination of two polymers provided adequate bioadhesive strength and fairly regulated the release profile up to 4 hr. The response surfaces and contour plots for each response parameter are presented for further interpretation of the results.The optimum formulations were chosen and their predicted results were found to be in close agreement with the experimental findings.